Obtenção de pós de Nb a partir da redução aluminotérmica com ignição por plasma - Mendes, Marcio Willians Duarte (2006)
The aluminothermic reduction consists in an exothermic reaction between a metallic oxide and aluminum to produce the metal and the scum. The extracted melted metal of that reaction usually comes mixed with particles of Al2O3 resulting of the reduction, needing of subsequent refine to eliminate the residual impure as well as to eliminate porosities. Seeking to obtain a product in powder form with nanometric size or even submicrometric, the conventional heat source of the reaction aluminothermic , where a resistor is used (ignitor) as ignition source was substituted, for the plasma, that acts more efficient way in each particle of the sample. In that work it was used as metallic oxide the niobium pentoxide (Nb2O5) for the exothermal reaction Nb2O5 + Al. Amounts stoichiometric, substoichiometric and superestoichiometric of aluminum were used. The Nb2O5 powder was mixed with aluminum powder and milled in planetarium of high energy for a period of 6 hours. Those powders were immerged in plasm that acts in a punctual way in each particle, transfering heat, so that the reaction can be initiate and spread integrally for the whole volume of the particle. The mixture of Nb2O5 + Al was characterized through the particle size analysis by laser and X-ray diffraction (DRX) and the obtained product of reaction was characterized using the electronic microscopy of sweeping (MEV) and the formed phases were analyzed by DRX. Niobium powders with inferior sizes to 1 mm were obtained by that method. It is noticed, through the analysis of the obtained results, that is possible to accomplish the aluminothermic reduction process by plasma ignition with final particles with inferior sizes to the original oxide